2020
DOI: 10.3390/ijerph17061889
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Sleep among Residents in Long-Term Care Facilities

Abstract: Long-term care residents often experience sleep disturbances as they are vulnerable to a variety of physical, psychosocial, and environmental factors that contribute to sleep disturbances. However, few studies have examined the combined impact of multiple factors on sleep among long-term care residents. This study aimed to identify the factors that influence sleep efficiency and sleep quality based on a modified senescent sleep model. A total of 125 residents were recruited from seven long-term care facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Undoubtedly this is an important pathway to the delay or development of CVD and death. As regards behavioral factors, people with functional limitations in ADLs or IADLs were more likely to report smoking (52), lower level of physical activity (53), and lower sleep efficiency or irregular sleep (54), which in turn are risk factors for CVD and all-cause mortality (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly this is an important pathway to the delay or development of CVD and death. As regards behavioral factors, people with functional limitations in ADLs or IADLs were more likely to report smoking (52), lower level of physical activity (53), and lower sleep efficiency or irregular sleep (54), which in turn are risk factors for CVD and all-cause mortality (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the wristband-type consumer PATs are not practical for comparative assessment with others, but that they can be used for capturing changes within the user [38][39][40]. It is known that if appropriate support is not provided to the patient population undergoing rehabilitation, mortality and the degree of long-term care may worsen due to a decrease in physical activity and disrupted sleep cycle, leading to irregular daytime sleeping [3,4,41]. In addition, using a device that needs to be attached/detached or charged during the day (e.g., waist-type or cumbersome size) may be difficult due to deteriorated physical function, or the risk of forgetting to wear or losing it due to cognitive problems [13].…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, there are potential benefits in terms of reduced nighttime disturbances, though room sharing may not a primary driver of poor sleep among nursing home residents. 25 The primary cost associated with decreasing crowding is financial, with estimated construction costs of single-bed rooms being 44% higher per bed compared to 2-bed rooms and 82% higher per bed compared to 4-bed rooms. 24 Further, nursing staff in hospitals indicate that one perceived benefit of shared rooms are decreased walking distances during nursing shifts.…”
Section: Discussionmentioning
confidence: 99%